2008
DOI: 10.1177/1557988308322299
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Drugs: High-Risk Behaviors at Circuit Parties

Abstract: 344risky behavior and to recommend an evidence-based approach for behavioral counseling to reduce risk for sexually transmitted infection (STI) and HIV transmission at CP venues. Search StrategyFor this literature review, searches were conducted on CINAHL, MedLINE, and PubMed using the following key words: circuit party, men who have sex with men (MSM), club drugs, gay men, unsafe sex, unprotected sex, drug use, sexually transmitted infections, and HIV. Although other medical and psychological comorbidities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Known risk behaviors associated with HIV infection and that could be “transmitted” through a social network include sex-drug use (SDU) 38 and unprotected anal intercourse (UAI). Moreover, group sex (GS) has also recently gained increased attention as an important risk practice 39,40 which can complicate network analysis. 41 Important influences and practices such as these, however, have not been previously explored through social network analysis within BMSM despite this population’s position as a group with the highest risk of HIV infection in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Known risk behaviors associated with HIV infection and that could be “transmitted” through a social network include sex-drug use (SDU) 38 and unprotected anal intercourse (UAI). Moreover, group sex (GS) has also recently gained increased attention as an important risk practice 39,40 which can complicate network analysis. 41 Important influences and practices such as these, however, have not been previously explored through social network analysis within BMSM despite this population’s position as a group with the highest risk of HIV infection in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Shooting galleries have been widely studied as HIV risk environments for people who inject drugs (Friedman & Aral, 2001; Klein & Levy, 2003; Rhodes, 2002; Rhodes et al, 2005), crack houses as risk environments for unsafe sex and for risk reduction efforts (Inciardi, 1996; Maher, 1997; Ross et al, 1999; Sterk, 1999, 2000; Williams, 1992), brothels for sex workers and others (Deren et al, 1996; Remple et al, 2007), and bathhouses, public cruising areas and circuit parties as environments conducive to drug use and high-risk sex among gay men (Binson et al, 2001; Choi et al, 2004; Ghaziani & Cook, 2005; Grierson, Smith, & von Doussa, 2008; Ostrow & Stall, 2008; Weidel, Provencio-Vasquez, & Grossman, 2008; Wohlfeiler & Potterat, 2005). This article discusses group sex events—defined as events at which some people have sex with more than one partner—as risk environments, with a particular focus on group sex events where people who take heroin, cocaine or crack by non-injection routes of administration take part and where the event is not primarily LGBT-identified, at a classic crack house, nor in a brothel.…”
Section: Introductionmentioning
confidence: 99%
“…3,[20][21][22] Moreover, MSM who attend bathhouses, party-oriented events (e.g., circuit parties), and gay-destination vacations and use the Internet to find sexual partners often report using substances with sex. [26][27][28][29][30][31] Although prior studies have identified a variety of common risk factors of MSM who use substances with sex, few studies have examined substance use with sex among male couples. For instance, one study described partnered MSM as being more likely to report using substances than those without a main partner; substance use was also associated with main partners having had UAS outside of their relationship.…”
Section: Introductionmentioning
confidence: 99%